2015
DOI: 10.1097/scs.0000000000001969
|View full text |Cite
|
Sign up to set email alerts
|

Finite Element Analysis of Bone Stress for Miniscrew Implant Proximal to Root Under Occlusal Force and Implant Loading

Abstract: Because of the narrow interradicular spaces and varying oral anatomies of individual patients, there is a very high risk of root proximity during the mini implants inserting. The authors hypothesized that normal occlusal loading and implant loading affected the stability of miniscrew implants placed in proximity or contact with the adjacent root. The authors implemented finite element analysis (FEA) to examine the effectiveness of root proximity and root contact. Stress distribution in the bone was assessed at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The peak values of stress and displacement within the bone around the implant neck and the surrounding bone close to the tooth root increase significantly as the distance between the implant and the root decreases. However, when a load is applied to the implant separately, the relationship between implant stability with the proximity of the mini-implant to the adjacent root is unclear 18) . To date, no studies have evaluated the effects of different loading conditions on the clinical stability of mini-implants close to tooth root.…”
Section: Introductionmentioning
confidence: 99%
“…The peak values of stress and displacement within the bone around the implant neck and the surrounding bone close to the tooth root increase significantly as the distance between the implant and the root decreases. However, when a load is applied to the implant separately, the relationship between implant stability with the proximity of the mini-implant to the adjacent root is unclear 18) . To date, no studies have evaluated the effects of different loading conditions on the clinical stability of mini-implants close to tooth root.…”
Section: Introductionmentioning
confidence: 99%
“…When it comes to MRP, Shan et al 19 suggested that normal occlusal loading might bring some micromotion to MSI and influence its stability, and the distance between the MSI and the adjacent root was recommended to be at least 1 mm. Some previous clinical studies concluded that inadequate space between MSI and root was considered as one of the major risk factors for MSI failure 1,20,21 .…”
Section: Discussionmentioning
confidence: 99%
“…A high number of studies present the use of FEA in oral implantology. They evaluate biomechanical aspects [59,60,61,62,63] but also tissue-related issues [64,65,66,67,68]. Such tests might provide only partially relevant information since the accurate definition of tissue parameters is impossible.…”
Section: Discussionmentioning
confidence: 99%